High-Flow vs. Low-Flow Nasal Cannula in Reducing Hypoxemic Events During Bronchoscopic Procedures: A Systematic Review and Meta-Analysis - Sampsonas, Fotios; Karamouzos, Vasileios; Karampitsakos, Theodoros; Papaioannou, Ourania; Katsaras, Matthaios; Lagadinou, Maria; Zarkadi, Eirini; Malakounidou, Elli; Velissaris, Dimitrios; Stratakos, Grigorios; Tzouvelekis, Argyrios (Frontiers in Medicine, 2022)
ABSTRACT Introduction High Flow Nasal Cannula (HFNC) oxygenation method has been proven to be successful in oxygenation of patients with respiratory failure and has exhibited clinical superiority compared to Low Flow Nasal Cannula (LFNC). Methods We performed a systematic review and metanalysis to evaluate the potential favorable impact of the HFNC oxygenation during bronchoscopy and related procedures like Endobronchial Ultrasound-Transbronchial Needle Aspiration. Only Randomized Control Trials (RCTs) were finally included in the metanalysis. Results Six randomized control trials with 1170 patients have been included in this metanalysis. Patients that underwent bronchoscopy with the use of High Flow Nasal Cannula experienced less hypoxemic events/desaturations, less procedural interruptions and pneumothoraxes compared to patients under Low Flow Nasal Cannula treatment. This beneficial effect of HFNC in hypoxemic events was persistent 10’ after the end of procedure. Conclusion HFNC oxygenation method could reduce hypoxemic events and related peri- and post bronchoscopic complications.